Occupational Therapy Drawing in Patients with Auditory Hallucinations: Descriptive Case Study Approach - Parapaga, Noviyanti; Ningrum, Puspita; Woran, Develin; Wowor, Marshanda C (LPPM STIKes Muhammadiyah Ciamis, 2025)
Mental disorders are someone who shows changes in behavior and symptoms in thoughts and feelings that cause suffering and prevent them from carrying out activities as they should. Hallucinations are one of the most common mental disorders suffered by hallucination patients, there are various kinds such as auditory, visual, tactile, gustatory, and olfactory hallucinations. The implementation strategy is occupational drawing therapy given to auditory hallucination patients which aims to control hallucinations. The purpose of this case study is Occupational Drawing Therapy in Patients with Auditory Hallucination Problems at Prof. Dr. V. L. Ratumbuysang Mental Hospital, North Sulawesi Province to get an overview of occupational drawing therapy in auditory hallucination patients. The method used is descriptive using a case study approach. Obtained from the application of occupational drawing therapy on 2 subjects, namely verbalization of hearing whispers, sensory distortion, hallucinatory behavior, and decreased daydreaming. Occupational drawing therapy as a complementary therapy in patients with auditory hallucinations is useful for self-control. This case study expected nurses areo apply occupational drawing therapy as part of nursing interventions in patients with sensory perception disorders, especially auditory hallucinations.